Prevalence of Latent and Active Tuberculosis Infection in Inflammatory Bowel Disease Patients Who Received Biological Treatment
Background/Aims: This study aims to assess the frequency of latent tuberculosis (TB) and the incidence of active TB infection in patients with inflammatory bowel disease (IBD) and Behçet’s syndrome with gastrointestinal involvement who received either tumor necrosis factor–alpha (TNF-α) antagonist therapy or vedolizumab as a second-line biologic treatment following TNF-α antagonist therapy. Materials and Methods: A total of 349 patients were included in the study. Demographic data, disease characteristics, TB screening results, prophylactic treatment regimens and the duration, as well as side effects were collected from patient records. Results: Among the patients, 196 (56.1%) were male, with a mean age of 42 years and a mean disease duration of 10 Å